Effect of Intensity of Accessing Internet, Sales Promotion, and Positive Emotions on Impulsive Buying - Tirtaning, Kinanti Sekar; Setiaji, Khasan (Universitas Negeri Semarang, 2021)
This study aimed to analyze the effect of internet access intensity, sales promotion, and positive emotions on impulsive buying in the marketplace. The research approach used a quantitative approach. The population in this study were students of Universitas Negeri Semarang, Class of 2016-2019. The number of samples in this study was 385 respondents who were calculated by using the infinite population slovin formula. The sampling technique used accidental sampling. The method of collecting data used a questionnaire. The results of this study indicated that there was an effect of the intensity of accessing the internet on impulsive buying, giving a partial effect of 4.93%. Sales promotion on impulsive buying had a partial effect of 7.40%. Positive emotions towards impulsive buying gave a partial contribution of 2.31%. There was an effect of the intensity of accessing the internet, sales promotion, and positive emotions on impulsive buying, giving a simultaneous effect of 37.2%. The suggestion of this research is that students are expected to make better use of their time so that they are not wasted just to access the marketplace, do shopping planning, prioritize needs rather than wants.